COMPREHENSIVE REVIEW OF THE PSYCHOLOGICAL IMPACT OF RADIATION TREATMENT ON CANCER PATIENTS. - Khalid Marzook Alharbi Hmoud Owaibd Almotary, Alaa A.Whaba.Elah Almotea, Daifallah Meshal Alharbi, Bader. Mazkar. Almutairi, Abdulrahman Mohammed Alkhaibari, Mohammed Moalla Ali Alaofi, Ali Dkheelallah Almutairi (Chelonian Research Foundation, 2022)
In the treatment of cancer patients, radiation therapy is a method with high fidelity. However, it may produce psychological stress. This detailed review addresses the psychological effects of radiation therapy on cancer patients, looking at the different factors, for example, anxiety, depression, wellbeing, and coping ways. Through an extensive analysis of available literature just for cancer patients going through radiation treatment, this review attempts to provide you with the psychological requirements made by cancer patients during radiotherapy. As a result, the latter part of the paper forwards this psychological effects containment and criticizes the facilitation of patient well-being wellbeing, with the final aim of improving the general cancer care experience. Keywords: Radiation treatment, Cancer patients, Psychological impact, Anxiety, Depression, Quality of life, Coping mechanisms